The Relevance of the Tatamba Mantra Manuscript and Family Medicinal Plants (TOGA) in the Baduy Indigenous Community - Elis Suryani Nani Sumarlina; Rangga Saptya Mohamad Permana; Undang Ahmad Darsa; Wina Erwina; Abdul Rasyad (Universitas Hamzanwadi, 2024)
Sundanese manuscripts are still relatively unknown in today's society. Perhaps it is regarded a new science with no benefit to scientific development. In truth, manuscripts and writings as subjects of philological study have been known in Alexandria from the third century BC, according to a character named Erasthothenes. Manuscripts as cultural documents and literary references for other sciences must be made aware of their existence in the current millennium, as many manuscripts' contents remain unknown. One of them is Family Medicinal Plants (TOGA), which is revealed in the manuscript text of the Tatamba mantra and is used by the Baduy indigenous community to boost endurance and immunity. The Tatamba manuscript's significance to Baduy TOGA must be maximized in order to determine the kind, function, dose, processing technique, and therapy actions, as well as the usage of TOGA for health maintenance based on the Tatamba manuscript. Descriptive research, comparative analysis, and text criticism study methodologies, as well as codicology and textology, pharmacology, health communication, and transdisciplinary cultural studies, were investigated. TOGA in the Tatamba mantra manuscript is relevant to the lives of the Baduy indigenous community because it is supported by the ngukus tradition, which is a ngajampé ceremony'reciting mantras' to pray for the safety, health, and welfare of the Baduy indigenous community, which is performed once a year when the ngalaksa tradition is carried out. This topic is relevant not only to philology, but also to other multidisciplinary fields such as agriculture, pharmacy, medicine, cultural communication, anthropology, and public health.